PENERAPAN ALGORITMA REGRESI LINEAR BERGANDA PADA APLIKASI MONITORING DAN PELAPORAN KEUANGAN UMKM DI DINAS KOPERASI DAN UMKM MINAHASA - La'bi', Eva Rivalda Pappang; Kenap, Audy A; Hasibuan, Alfiansyah A (Journal of Innovation And Future Technology (IFTECH), 2024)
This research aims to design and build a financial monitoring and reporting application for Micro, Small and Medium Enterprises (MSMEs) at the Minahasa Cooperatives and UMKM Service. With the significant number of MSMEs in Minahasa, it is important for the department to monitor the use of the start-up entrepreneur program assistance funds provided to MSMEs. However, problems in the financial monitoring and recording system still occur, requiring improvements through the application of technology. Linear regression algorithms are used to identify MSMEs that still have the potential to obtain further funding, in accordance with the criteria determined by the department. The application that was built aims to increase transparency in the use of aid funds, make it easier for the department to evaluate the sustainability of MSME businesses, and ensure that funding is then distributed to MSMEs which have a positive impact on local economic growth. This application is an important tool in supporting. the development and growth of MSMEs and the local economy overall.